The changes in the chemical forms of thallium, cobalt and manganese with air-drying of soils. Issue 4 (4th July 2022) - Narukawa, Takahiko; Makino, Tomoyuki; Kanno, Hitoshi; Hamamoto, Toru; Kimura, Kazuhiko; Yamasaki, Shin-Ichi
ABSTRACT: Thallium (Tl) is a highly toxic metal that induces pathological changes in organs. Many Tl-contaminated soils have been reported worldwide due to the releases of Tl from mineral weathering and mining industry. There is, however, limited information related to the dynamics and analysis of Tl in soil, since Tl is one of the emerging soil contaminants. Tl and cobalt (Co) are specifically adsorbed by manganese (Mn) oxide. On the other hand, air-drying of soils causes the dissolution of Mn oxide and the elution of heavy metals such as Co occluded by Mn oxide. Thus, the Mn oxide dissolution with air-drying is expected to affect the chemical forms of Tl with high sorption affinity to Mn oxide. We conducted the sequential extraction method using moist and air-dried soils. Air-drying caused the increases in Mn and Co in the exchangeable and acid soluble fractions, respectively, and the decreases in those in the Mn oxide occluded fraction, which is consistent with previous reports. Our research revealed that the exchangeable Tl increased and sum of the acid-soluble and Mn oxide occluded Tl decreased due to air-drying. The increments in the exchangeable fraction and the decrements in acid-soluble and Mn oxide occluded fractions were almost the same. Consequently, the increase in exchangeable Tl could be attributed to the other two fractions, indicating that soil Tl is sensitive to the soil drying.